Psychological wellbeing of family caregivers with schizophrenia patient - Frizzell, Nurdinie Asfa; Madon, Zainal (Human Resource Management Academic Research Society, 2022)
A person with good psychological wellbeing is a person who able to live with positive impression and can work well in their daily life (Huppert, 2009). This study aims to explore the challenges, support system and coping mechanism of family caregivers who are taking care of their family members with schizophrenia living in Klang Valley. Nine caregivers have participated in an in-depth interview session through online platform. Five themes have been generated consisting of 11 sub-themes. Five themes generated are such as guardian role, challenges faced by caregivers, emotion expression, support system and coping mechanism. Caregivers have been facing with various challenges with some are lacking with efficient support system. Caregivers did not get enough information related to schizophrenia from professionals that led them to search that information by their own. As a conclusion, caregivers need more information and guidance from professionals in order to allow them to provide better care for patient and at the meantime, able to help them in getting better psychological wellbeing.